In vivo Anti-inflammatory Activity of Lipidated Peptidomimetics Pam-(Lys-βNspe)6-NH2 and Lau-(Lys-βNspe)6-NH2 Against PMA-Induced Acute Inflammation - Wu, Bing C.; Skovbakke, Sarah L.; Masoudi, Hamid; Hancock, Robert E. W.; Franzyk, Henrik (Frontiers in Immunology, 2020)
Host Defense Peptides (HDPs) are key components of innate immunity that exert antimicrobial, antibiofilm and immunomodulatory activities in all higher organisms. Synthetic peptidomimetic analogs were designed to retain the desirable pharmacological properties of HDPs while having improved stability toward enzymatic degradation, providing enhanced potential for therapeutic applications. Lipidated peptide/β-peptoid hybrids [e.g., Pam-(Lys-βNspe)6-NH2 (PM1) and Lau-(Lys-βNspe)6-NH2 (PM2)] are proteolytically stable HDP mimetics displaying anti-inflammatory activity and formyl peptide receptor 2 antagonism in human and mouse immune cells in vitro. Here PM1 and PM2 were investigated for their in vivo anti-inflammatory activity in a phorbol 12-myristate 13-acetate (PMA)-induced acute mouse ear inflammation model. Topical administration of PM1 or PM2 led to attenuated PMA-induced ear edema, reduced local production of the pro-inflammatory chemokines MCP-1 and CXCL-1 as well as the cytokine IL-6. In addition, diminished neutrophil infiltration into PMA-inflamed ear tissue and suppressed local release of reactive oxygen and nitrogen species were observed upon treatment. The obtained results show that these two peptidomimetics exhibit anti-inflammatory effects comparable to that of the non-steroidal anti-inflammatory drug indomethacin, and hence possess a potential for treatment of inflammatory skin conditions.